2016
DOI: 10.1038/nm.4173
|View full text |Cite
|
Sign up to set email alerts
|

Purinergic receptors in the carotid body as a new drug target for controlling hypertension

Abstract: Given the proportion of individuals with resistance to, and poor compliance or tolerance of, antihypertensive medication new drugs to treat this syndrome are required urgently. We show that peripheral chemoreceptors generate aberrant signalling contributing to high blood pressure in hypertension and thus reveal a novel target. We discovered that P2x3 receptor mRNA expression was up regulated substantially in chemoreceptive petrosal sensory neurones in hypertensive rats. These neurones generated both tonic driv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
173
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 158 publications
(193 citation statements)
references
References 59 publications
9
173
0
Order By: Relevance
“…Moreover, previous studies have evidenced that severe loss of A5 neurons in the A5 area contributes to the manifestation of autonomic disorder associated with the neurodegenerative disease of multiple system atrophy (Benarroch et al, 2008). These observations open the possibility that changes in the functioning of A5 neurons may underpin the development of augmented sympathetic levels, especially in pathological conditions associated with hyperactivity of peripheral chemoreceptors, such as obstructive sleep apnea (Narkiewicz et al, 1998), heart failure (Toledo et al, 2017) and neurogenic hypertension (Pijacka et al, 2016). …”
Section: Discussionmentioning
confidence: 99%
“…Moreover, previous studies have evidenced that severe loss of A5 neurons in the A5 area contributes to the manifestation of autonomic disorder associated with the neurodegenerative disease of multiple system atrophy (Benarroch et al, 2008). These observations open the possibility that changes in the functioning of A5 neurons may underpin the development of augmented sympathetic levels, especially in pathological conditions associated with hyperactivity of peripheral chemoreceptors, such as obstructive sleep apnea (Narkiewicz et al, 1998), heart failure (Toledo et al, 2017) and neurogenic hypertension (Pijacka et al, 2016). …”
Section: Discussionmentioning
confidence: 99%
“…Within the carotid body, the transduction of hypoxia to afferent discharge depends, in part, on ATP release and activation of P2 receptors. 45,46 Purinergic receptor plasticity was revealed in chemoreceptive petrosal afferent neurons in hypertension. Selective blockade of these receptors reduced arterial pressure and may be a novel therapeutic target for hypertension.…”
Section: Reflex Control Of the Cardiovascular Systemmentioning
confidence: 99%
“…Recent studies have shown that there is an antihypertensive effect of P2X3 receptor antagonists, because of inhibition of sympathetic nerve activity via increased peripheral chemoreceptor reflex sensitivity involving the carotid body. 46 Microinjections of the selective P2X3 (as well as P2X1) receptor antagonist, α,β-meATP, into the dorsal facial area of the medulla increased common carotid artery blood flow. 162 Therefore, P2X3 receptor antagonists are being explored for the treatment of hypertension.…”
Section: Vascular Diseasesmentioning
confidence: 99%
“…Indeed, Pijacka et al . () found that antagonism of P2X3 receptors reduced BP, basal sympathetic activity and normalized enhanced CB hyperreflexia in conscious rats with hypertension, while no effect was observed in rats without hypertension. On the other hand, Del Rio et al .…”
Section: Introductionmentioning
confidence: 97%